Outcome of Allogeneic Hematopoietic Stem Cell Transplantation in Acute Myeloid Leukemias with Hyperdiploid Karyotype - TL Gindina; NN Mamaev; ES Nikolaeva; SN Bondarenko; OA Slesarchuk; AS Borovkova; SV Razumova; OV Pirogova; AL Alyanskii; LS Zubarovskaya; BV Afanas’ev (Kliničeskaâ onkogematologiâ, 2016)
Aim. To evaluate the prognostic impact of the different cytogenetic characteristics, including the modal number, the number of chromosomal aberrations in a complex karyotype, and adverse chromosomal abnormalities (ACA) (–7/7q–, –5/5q–, –17/17p–, t(6;9)(p22;q34)) on the results of allogeneic hematopoietic stem cell transplantation (allo-HSCT) in patients with hyperdiploid acute myeloid leukemia (H-AML). Methods. Forty seven H-AML patients (21 women and 26 men, aged from 1 to 58 years, median — 23.9 years) were examined. The analysis of overall (OS) and event-free survival (EFS) predictors after allo-HSCT in patients with different clinical, transplant and cytogenetic characteristics was performed. Results. The modal number of chromosomes (MN) of 47–48 was the most common one in the karyotype which was observed in 31 (66 %) patients. High hyperdiploidy with the modal number of 49–65 was identified in 13 (28 %) patients, near-triploid and near-tetraploid karyotypes were found in 3 (6 %) patients. Quantitative chromosomal abnormalities were nonrandom. Chromosome 8 (50 %), 21 (32 %), 13 (16 %) и 22 (16 %) trisomy was the most common one. Structural chromosomal abnormalities were detected in 22 (47 %) patients, at that, ACA were found in 7 (19 %) patients. In univariate analysis, the OS and EFS after allo-HSCT differed in patients with different clinical status (remission vs. active disease; p = 0.003 and p = 0.002, respectively), different chromosomal abnormalities in hyperdiploid karyotype (ACA– vs. ACA+; p = 0.001 and p = 0.03, respectively). An additional analysis of selected patients group with a structurally complex karyotype (n = 19) showed, that patients without ACA had a higher OS than patients with ACA (p = 0.03). In multivariate analysis, the disease status (relapse) at allo-HSCT was an independent predictor of decreased OS and EFS (p = 0.004 и p = 0.006, respectively), as well as the presence of the ACA (p = 0.002 only for OS). Conclusion. ACA were high-risk factors in H-AML patients received allo-HSCT. Therefore, the patients with formal criteria of a complex karyotype should not be automatically included in the cytogenetic unfavorable risk group.